Knowledge, attitudes and binge drinking among urban Chinese university students in Hong Kong. (30th September 2020) - Kim, J; Yu, J Z; Chan, R H W; Leung, K L; Sumerlin, T S; Fong, B; Siu, S; Lee, J J; Chung, R Y
Abstract: Background: Although dormitory residents have been identified as a high-risk group for alcohol misuse in Chinese university settings, the factors associated with their drinking behaviors has not be characterized. Methods: A cross-sectional study was conducted among hostel residents in two Hong Kong universities (n = 1455) using self-administered, anonymous surveys. In addition to examining the knowledge levels and drinking-related attitudes, we examined the factors associated with binge drinking in this population using multivariable regression analysis. Results: Among university dormitory residents, the prevalence of past-month binge drinking was 26.8% among males and 12.8% among females. It was noted that although respondents demonstrated attitudes conducive towards alcohol-free socialization, they exhibited low levels of alcohol-related knowledge (mean knowledge score: 3.3/ 10, SD = 2.0). While about 59% were aware that alcohol is a carcinogen and that some medications should not be taken with alcohol, only 10.4% were familiar with symptoms of alcohol poisoning and only 23% were familiar with relative amounts of alcohol in different beverage categories. Of the respondents the factors independently associated with past-month binge drinking were: male sex, older age, full-time hostel residence, drinking roommates, drinking romantic partner, participation in drinking games, and having pro-alcohol attitudes (OR ranging from 1.33-3.69). Alcohol-related knowledge was not associated with binge drinking. Conclusions: Although southern China is a low alcohol consumption area, binge drinking is common among university residents and requires multi-prong interventions. Heavy drinking is a neglected health problem among urban Chinese university students. Interventions targeting binge drinkers need to counteract pro-alcohol attitudes and peer effects. Increasing alcohol knowledge may additionally help to reduce alcohol-related harms in this age group. Key messages: Urban Chinese university dormitory residents demonstrate low levels of alcohol knowledge. Pro-alcohol attitudes and peers effects need to be addressed in university anti-binge drinking interventions.